Description of five new Lophocampa Harris from the Dominican Republic (Lepidoptera, Erebidae, Arctiinae) - Vincent, Benoit (Zootaxa, 2020)
Five new species of Lophocampa are described from the Dominican Republic. Lophocampa occidentalis n. sp. is described from two males, Lophocampa perezgelaberti n. sp. from three males and two females, Lophocampa desotoi n. sp. from seven males and two females, Lophocampa sharki n. sp. from three males and Lophocampa flavoabdominalis n. sp. from five males and one female. The habitus and genitalia are illustrated. A comparison with closest species is proposed on morphological and molecular characters.